2018
DOI: 10.1039/c7ra12064h
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of the methanesulfonate–ammonia/amine complex and its atmospheric implications

Abstract: Methanesulfonate (MSA À ), found in substantial concentrations in the atmosphere, is expected to enhance aerosol nucleation and the growth of nanoparticles, but the details of methanesulfonate clusters are poorly understood. In this study, MSA À was chosen along with ammonia (NH 3 ) or three common amines and water (H 2 O) to discuss the roles of ternary homogeneous nucleation and ion-induced nucleation in aerosol formation. We studied the structural characteristics and thermodynamics of the clusters using den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 91 publications
(116 reference statements)
1
12
0
Order By: Relevance
“…By comparing five atmospherically relevant amines, Yu et al concluded that the enhancing effect of amine on particle formations and growth strongly depended on its basicity. Similar conclusions were obtained by Glasoe et al and Myllys et al Accordingly, it is widely accepted that amines are key stabilizers for sulfuric acid-containing clusters, ,, and the corresponding complex stability and particle formation rate were determined by the base strength of amines. However, Jen et al found in experiments that the stabilizing ability of methylamine on the formation of sulfuric acid–amine dimers was weaker than that of trimethylamine (TMA) and dimethylamine (DMA), while the enhancing abilities of the latter two were close, which was slightly opposite to the fact that TMA is the strongest base in the gas phase.…”
Section: Introductionsupporting
confidence: 85%
“…By comparing five atmospherically relevant amines, Yu et al concluded that the enhancing effect of amine on particle formations and growth strongly depended on its basicity. Similar conclusions were obtained by Glasoe et al and Myllys et al Accordingly, it is widely accepted that amines are key stabilizers for sulfuric acid-containing clusters, ,, and the corresponding complex stability and particle formation rate were determined by the base strength of amines. However, Jen et al found in experiments that the stabilizing ability of methylamine on the formation of sulfuric acid–amine dimers was weaker than that of trimethylamine (TMA) and dimethylamine (DMA), while the enhancing abilities of the latter two were close, which was slightly opposite to the fact that TMA is the strongest base in the gas phase.…”
Section: Introductionsupporting
confidence: 85%
“…1 A mass of studies have shown that new particle formation (NPF) through gas-to-particle conversion is the main source of atmospheric aerosol particles and the leading uncertainties in global climate modeling and forecasting. [2][3][4] Sulfuric acid (SA) has been proved to be essential to initiate new particle formation in the atmosphere 2,5-8 through clustering with various nucleation precursors such as water (H 2 O), 9 ammonia (NH 3 ), [10][11][12] dimethylamine (DMA), 13,14 methylamine (MA), 15 monoethanolamine (MEA), 16 piperazine (PZ), 17 methanesulfonic acid, 18,19 nitric acid 20 and iodic acid. 21,22 However, it is not efficient enough to explain the particle formation rates observed in the atmosphere, suggesting that other compounds may participate in the nucleation process.…”
Section: Introductionmentioning
confidence: 99%
“…Atoms in molecules (AIM) theory 33 and the noncovalent interaction (NCI) index 34 are widely used to characterize noncovalent interactions. 12,25,35,36 The change in the atomic charge (q) at H atom was obtained by natural bond orbital theory (NBO) 37 (see Section 4 in the ESI †). All wavefunctions of the electron structures for the dimers and trimers were obtained at the B3LYP-D3/aug-cc-pVTZ level.…”
Section: Computational Detailsmentioning
confidence: 99%
“…18 The results of theoretical calculations by Miao et al indicate that amines can form more stable clusters with MSA À than with A. 25 Theoretical research shows that methyl hydrogen sulfate (MHS)-based and MSAbased trimers are more thermodynamically favorable and may participate in atmospheric NPF due to synergy between the base molecules. 26,27 To our knowledge, the effects of synergy between basic molecules on the binding energy and stability of the initial clusters involving MSA is still unclear at the molecular level, especially for MSA-base-base trimers.…”
Section: Introductionmentioning
confidence: 99%